2021
DOI: 10.35808/ijeba/672
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Network Ties on SMEs Internationalization Process in the Developing Countries Emerging Markets: A Comparison between Mongolia, China, and Malaysia

Abstract: Purpose:The paper aims to investigate the role of all types of networking on SMEs' internationalization process in general. Then, to compare SMEs' networking approaches in the selected three countries and their main differences in terms of network creation and operation. Finally, to report effective SMEs' internationalization practices in Malaysia and China, which should be adopted in Mongolia. Approach/Methodology/Design: The study is descriptive and used secondary data as the primary source. We concluded ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Even if SMEs in Mongolia generate 67% of the total job opportunity, produce 20% of GDP, and 2.3% of total export, SMEs create relatively low levels of value-added products or services and export share. But SMEs in both countries are ranked in a high position in regard to their magnitude and employment (Altnaa et al, 2021). In turn, in Kazakhstan, 96.3% of total registered businesses are SMEs, which provide 80.5% of total employment opportunities and contribute 24.8% to the total GDP (Ismail et al 2011;Turkyilmaz et al, 2021;Shaikh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Even if SMEs in Mongolia generate 67% of the total job opportunity, produce 20% of GDP, and 2.3% of total export, SMEs create relatively low levels of value-added products or services and export share. But SMEs in both countries are ranked in a high position in regard to their magnitude and employment (Altnaa et al, 2021). In turn, in Kazakhstan, 96.3% of total registered businesses are SMEs, which provide 80.5% of total employment opportunities and contribute 24.8% to the total GDP (Ismail et al 2011;Turkyilmaz et al, 2021;Shaikh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous empirical studies have shown that SMEs play a crucial role in the economic and commercial development of the world for various reasons (Altnaa et al , 2021). First, they develop the economy by creating economic growth, generating jobs, evolving technological capabilities, offering a range of products and reducing tax revenues (Hutchinson et al , 2009; Ngoma et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Second, SMEs help reduce poverty and income inequality based on their limited resources, especially in emerging and developing markets. Further, they represent over 90% of all businesses globally, and on average, generate more than 70% of total employment (Altnaa et al , 2021). According to the statistics of MIMT [1] of Iran (2021), the SMEs represented 98% of all businesses and 63% of employment in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates suggest that around 5.76 million SMEs were operating in the distributive trades sector (Wholesale and retail trade), and 1.2 million SMEs were in transport and storage trade [3]. This highlights the significance of SMEs in the economy in Europe, also in other regions in the world [4,5] and their potential to contribute to economic growth.…”
Section: Introductionmentioning
confidence: 99%